SIMULIIDAE (DIPTERA) DEL RÍO QUEQUÉN GRANDE EN LAS CASCADAS, (BUENOS AIRES, ARGENTINA): VARIACIÓN POBLACIONAL Y RELACIÓN CON TEMPERATURA, CAUDAL Y PRECIPITACIONES - Coscaron, S.; Coscaron-Arias, C. L.; Porcaro, G. (Acta Entomológica Chilena, 2022)
Quequén Grande is a river plain of the Southern area of Buenos Aires province; the river source is in the Tandilia mountain system and has a permanent flow. The area has a températe climate and rains are more or less uniformly distributed all over the year. Black fly larvae and pupae were sampled mostly biweekly during 26 monlhs at Las Cascadas area, about 15 km North Necochea city. Two species, Simulium (Psaroniocompsá) bonaerense Coscaron & Wygodzinsky and S. (Thyrsopelma) orbitale Lutz, were found. The former was more abundant and was present all along the year. Immatures density of S. bonaerense do not show correlation with temperature, precipitation or stream discharge. S. orbitale shows negative correlation with temperature.